Porous anisotropic metal nanostructures through controlled transmetallation across a dialysis membrane - Shukla, Sourabh; Pasricha, Renu; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2009)
Nanostructured metals with hollow interiors are of technological importance due to their unique optoelectronic properties and enhanced surface area. We describe herein, a novel method for the synthesis of anisotropic gold and palladium nanoparticles through a simple galvanic replacement reaction across a semi-permeable dialysis membrane. The control over the reaction kinetics achieved by the presence of membrane enables one to tune the bimetal composition, particle porosity and morphology. Rapid outward diffusion of silver ions generated from the sacrificial silver nanoparticles even at room temperatures prevents the precipitation of high quantities of silver chloride, thereby circumventing the need for product purification. The porous anisotropic nanostructures have potential applications in catalysis, cell imaging and therapeutics.
Keywords: Ag/Pd Nanostructures; Anisotropic Nanoparticles; Dialysis; Galvanic Replacement; Porous nanostructures; Silver Nanotriangles; Silver Nanowires; Transmetallation

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation